(untitled) (El Taco en la Brea, 2018)
At the turn of the twentieth century in the Río de la Pla- ta, intellectuals and writers of diverse ideological orien- tations thought about the function and the possibilities of Science in the context of a young nation. Their inter- ventions took place beyond the frames of positivism, and developed in other areas such as the magazines of local Spiritualism and Theosophy, and the fantastic literature based on scientific topics. Seeking to discuss the anachronistic polarizations be- tween Spiritualism and Scientism, and being aware of the wide grayscale between both terms present in the turn of the century culture, in this work I propose to analyze a series of essays and fictional texts written by Leopoldo Lugones, Emilio Becher and Carlos O. Bunge. No matter whether Bunge claimed himself a positivist intellectual, whether Becher and Lugones were identified with Spiritualism and Modernism, in their texts they all sought answers for what was further of the limits of positivist methodology. Moreover, they dreamed, in different ways, about a sort of global discipline that could gathered the modern scientific knowledge and the spiritualistic believes, the moral and the Ideal.